Occurrence of aflatoxin in agricultural produce from local markets in Burundi and Eastern Democratic Republic of Congo - Udomkun, Patchimaporn; Mutegi, C.; Assfaw Wossen, Tesfamicheal; Atehnkeng, J.; Nabahungu, N.L.; Njukwe, E.; Vanlauwe, Bernard; Bandyopadhyay, Ranajit (Wiley, 2018)
Aflatoxins are noxious secondary metabolites, of certain fungal species, found in food and feed. Contamination of a commodity with aflatoxins is associated with production and storage losses, and subsequently less food availability. Aflatoxins can also pose human health risks and represent a barrier to the development of trade, in both domestic and international markets. In this study, samples of cassava, maize, groundnut, beans, soybean, sorghum and milk, and their processed products were collected from local markets in Burundi and Eastern DRC. In order to investigate the levels of aflatoxin, crop samples were analyzed using a single step lateral flow immunochromatographic assay (Reveal Q+), while enzyme‐linked immune‐sorbent assay (ELISA) was used to analyze aflatoxin‐M1 in milk, yogurt, and cheese samples. The results revealed the presence of aflatoxins in all samples from both countries, with levels ranging from 1.3 to 2,410 μg/kg. Samples collected from Burundi contained relatively higher (p > 0.0.5) levels of aflatoxins. In 51% of all the crops samples, total aflatoxin contamination was above the EU maximum tolerable level of 4 μg/kg. Processed products, particularly from groundnut, maize, and sorghum, had the highest levels of aflatoxin contamination when compared to unprocessed grain. With regard to milk and dairy products, the level of aflatoxin‐M1 ranged from 4.8 to 261.1 ng/kg. Approximately 29% of milk and yogurt samples had aflatoxin‐M1 higher than the EU regulatory limit of 50 ng/kg, whereas 20% of cheese samples were found to be contaminated at levels higher than the maximum limit of 250 ng/kg. These results can serve as the basis for pre‐ and postharvest approaches to reduce aflatoxin contamination in agricultural commodities in Burundi and Eastern DRC in order to reduce health risk, avoid reduced production in livestock, and open up export markets.